Comparativo bibliográfico de la importancia de los polinizadores del género Apis para la generación de servicios ecosistémicos (captación de carbono), con base en resultados de la trashumancia en los cultivos comerciales. (2020)
The present work aims to make a comparison based on bibliographic bases that address the importance of pollinators of the genus ´´Apis´´ in the generation of ecosystem services (carbon sequestration) and environmental resilience Vs the results found in transhumance and cash crops. Initially, a general contextualization of ecosystem services is carried out until a focus is reached on carbon sequestration in different scenarios with different types of forest species, in this way we proceed to analyze the effects of directed transhumance with Apis bees on crops commercial varieties such as strawberry (Fragaria Chiloensis) where it increases from 74.5 +/- 20.25 kg to 151.3 +/- 20.25 kg after pollination, as is the case with coffee, increasing the tie by 14%. Once the data on the increase in leaf area and therefore of fruit for commercial crops has been established, a comparison of the floral and foraging aptitude of high mountain species is made, these species play an important role in the production of ecosystem services, especially in the carbon uptake from the amount of stomata present in the foliar area. For this reason, a proposal is made for a program that aims to measure ecological restoration (passive) through pollination with bees (Apis mellifera) located in systematically established plots, where it is possible to evaluate its incidence in floral tree species and species forests of interest for carbon sequestration.